Une définition du récit d’après Paul Ricœur - Annik Dubied (Communication)
In his work, Temps et récit, Paul Ricoeur envisages the narrative within the frame of his more global relections on interpretation. For Ricoeur, narrative is but one example among many, of the mediations which contribute, through their interpretation, to the understanding of the self ; the philosopher’s definition of which is apt to serve as the foundation for a definition of mediated narratology understood as the study of dynamic narratives viewed within their paths of mediation. This article proposes a schematicization of Ricœur’s definition of narrative, which while making available an analytical tool not offered a priori by the philosopher’s work, designs a solid base from which the definition of narrative might be adapted to the field of media.